Keadilan Distributif dalam Perspektif Hukum Islam dan Implementasinya pada Sengketa Harta Bersama: Keadilan Distributif dalam Perspektif Hukum Islam dan Implementasinya pada Sengketa Harta Bersama - Ramadhan, Taufiq; Ismail, Habib; Khotimah, Khusnul; Maulana, Muhamad Ridho; Durin, Ramzi (Yapilin Press, 2025)
The issue of justice in the distribution of joint property after divorce is still a crucial issue in Indonesia, both in the practice of religious justice and in the life of the Muslim community. This article discusses the concept of distributive justice from the perspective of Islamic law and its implementation in the settlement of common property disputes. The purpose of this study is to analyze the extent to which the principles of distributive justice derived from Islamic teachings, such as proportional justice, benefits, and gender equality, are applied in the practice of sharing common wealth. The method used is library research with a normative qualitative approach, examining some of the data obtained and then analysis is carried out by examining how the principles of distributive justice are formulated in Islamic legal theory and how their implementation is reflected (or even neglected) in the practice of resolving joint property disputes in court. The findings of the study show that in Islamic legal theory, the division of common property emphasizes the principle of justice based on the contributions and needs of each party, rather than merely equal distribution. In practice, the implementation of this principle often encounters obstacles, both due to the limitations of proof of economic contribution and cultural bias factors that are still strong in the community and the legal apparatus. In conclusion, the application of distributive justice in common property disputes requires a deep understanding of the principles of maqāṣid al-sharī'ah and innovation in proving contributions, so that the goal of substantive justice is truly achieved in every court decision.